A bibliometric analysis of leadership management - Bahri, Bahri; Sari, Utami Tunjung; Artha, Bhenu; Sari, Niken Permata; Supranta, Virginia Amelia; Raihan, Atha (Universitas Widya Mataram, 2025)
Being a leader means having to use the resources that are available to you, whether they be material or human, in order to achieve goals and maintain organizational unity. Analysts define leadership as the process by which one individual inspires a group of people to work together toward a single objective. The main objective of this study was to quantify and identify the current state of leadership management through bibliometric analysis, to identify emerging issues, and to lay the foundation for subsequent research in the area. We use bibliometric analysis with VOS Viewer and have outlined the research literature from 2013 to 2023 to demonstrate the outlook for leadership management. This paper resulting in a refined dataset of 3691 articles. This study provides an in-depth bibliometric analysis of leadership management, revealing the global research landscape, international collaboration, publication trends, research hotspots, and emerging frontiers. The global output of publications maintains a balanced growth, highlighting the active engagement in this field. The analysis recognizes leading researchers and institutions globally, with the United States standing out as a major contributor.